Association of Vegetable Nitrate Intake With Carotid Atherosclerosis and Ischemic Cerebrovascular Disease in Older Women. Issue 7 (July 2017) - Bondonno, Catherine P.; Blekkenhorst, Lauren C.; Prince, Richard L.; Ivey, Kerry L.; Lewis, Joshua R.; Devine, Amanda; Woodman, Richard J.; Lundberg, Jon O.; Croft, Kevin D.; Thompson, Peter L.; Hodgson, Jonathan M.
Abstract : Background and Purpose—: A short-term increase in dietary nitrate (NO3 − ) improves markers of vascular health via formation of nitric oxide and other bioactive nitrogen oxides. Whether this translates into long-term vascular disease risk reduction has yet to be examined. We investigated the association of vegetable-derived nitrate intake with common carotid artery intima-media thickness (CCA-IMT), plaque severity, and ischemic cerebrovascular disease events in elderly women (n=1226). Methods—: Vegetable nitrate intake, lifestyle factors, and cardiovascular disease risk factors were determined at baseline (1998). CCA-IMT and plaque severity were measured using B-mode carotid ultrasound (2001). Complete ischemic cerebrovascular disease hospitalizations or deaths (events) over 14.5 years (15 032 person-years of follow-up) were obtained from the West Australian Data Linkage System. Results—: Higher vegetable nitrate intake was associated with a lower maximum CCA-IMT (B=−0.015, P =0.002) and lower mean CCA-IMT (B=−0.012, P =0.006). This relationship remained significant after adjustment for lifestyle and cardiovascular risk factors ( P ⩽0.01). Vegetable nitrate intake was not a predictor of plaque severity. In total 186 (15%) women experienced an ischemic cerebrovascular disease event. For every 1 SD (29 mg/d) higher intake of vegetable nitrate, there was an associated 17% lower risk of 14.5-year ischemic cerebrovascular disease events in both unadjusted and fully adjusted models ( P =0.02). Conclusions—: Independent of other risk factors, higher vegetable nitrate was associated with a lower CCA-IMT and a lower risk of an ischemic cerebrovascular disease event. Abstract : Supplemental Digital Content is available in the text.